(untitled) (One Health & Risk Management, 2021)
Introduction. The contemporary student lives in an extremely unstable and unpredictable society, from all points of view and deficient in terms of sharing positive emotions. The continuous changes occurring in a student’s life require constant efforts, actions, visions, attitudes and new skills that he/she must develop in order to keep pace with the world and at the same time be useful to the society of which he is part. Lots of research has been done on stress among students, especially those involving medical, pharmacy and dentistry students. Fewer research is found on the stress of students studying in a foreign country, in a different language than the native one. Students find it challenging to adapt to a new way of life, to learn to cope on their own, starting with cooking and ending with all sorts of new things, which at home were usually performed by their parents, brothers and sisters. Material and methods. The research was based on comparing the level of stress among local and international students, using a questionnaire with 2 standardized tests (Test to identify instructional stress; Test of inventory of stress symptoms). The study involved 114 people: 51 local students and 63 international students. Results. The study findings show that the local students report a double score for all the complaints related to the instructional process. The complaints presented by the students indicate large variations in the score for various complaints at local students, with scores between 3.2 and 7 points (out of a maximum of 10 points). In the case of international students, even if the scores are lower for all the complaints presented, the amplitude of the variations is not large, being registered between 2.0 and 2.8 points (out of a maximum of 10 points). The highest score for the complaints presented by local students was the feeling of constant lack of time (7 points out of 10) , whereas for international students three groups of complaints ranked first viz. headaches; increased irritability, upset and distraction; (2.8 out of 10 points). On the second place, the complaints regarding the quality of sleep among the local students were registered (6.7 points out of 10), whereas among the international students - the irrelevant thoughts (2.7 points out of 10). Low work capacity and increased fatigue were ranked third among local students (6.5 points out of 10), while international students reported insufficient sleep, poor quality and lack of time (2.6 points out of 10). The inventory of stress symptoms showed that local students are more stressed than international ones. About a third of local students are exhausted, they have irreversible consequences due to stress. Most local students feel severe (39.2%) and pronounced (21.5%) stress. Only 5.9% of local students experienced moderate stress and 3.9% were not stressed. Half of the international students are stressed, and a quarter of students have moderate stress. Stress is missing in only a quarter of international students. Conclusions. Both the Instructional Stress Identification Test and the Inventory of Stress Symptoms recorded a higher level of stress among local students rather than in international ones. Early detection of symptoms is important to prevent stress. The interdependent relationship between the perceived stress and symptoms of anxiety and depression suggests that one of the prevention strategies could even be the stress detection among first-year medical students.